Experimental Investigation of Flow Resistance in a Coal Mine Ventilation Air Methane Preheated Catalytic Oxidation Reactor - Bin Zheng; Yongqi Liu; Ruixiang Liu; Jian Meng; Mingming Mao (Journal of Chemistry)
This paper reports the results of experimental investigation of flow resistance in a coal mine ventilation air methane preheated catalytic oxidation reactor. The experimental system was installed at the Energy Research Institute of Shandong University of Technology. The system has been used to investigate the effects of flow rate (200 Nm3/h to 1000 Nm3/h) and catalytic oxidation bed average temperature (20°C to 560°C) within the preheated catalytic oxidation reactor. The pressure drop and resistance proportion of catalytic oxidation bed, the heat exchanger preheating section, and the heat exchanger flue gas section were measured. In addition, based on a large number of experimental data, the empirical equations of flow resistance are obtained by the least square method. It can also be used in deriving much needed data for preheated catalytic oxidation designs when employed in industry.